MENINGKATKAN KEMAMPUAN TEKNIK LOMPAT JAUH GAYA JONGKOK DENGAN MENGGUNAKAN ALAT BANTU TALI RINTANGAN DI KELAS VII-3 SMP NEGERI VII-3 SMP NEGERI 1 PATUMBAK TAHUN PELAJARAN 2018/2019 - Daslan Gultom (Universitas Islam Negeri Sumatera Utara Medan, 2020)
Long jump skills are one of the athletic branches that must be given to students of class VII-3 SMP Negeri 1 Patumbak. The ability of students' cognitive factors in understanding movement techniques that must be done in long jump really contributes to the achievement of optimal jump results. The long jump skills of Class VII-3 students of SMP Negeri 1 Patumbak are very low, this situation is very far from the author's expectation as a sports teacher by looking at the long jump participants' score on the Porseni which is 460 cm, this makes the author interested in conducting research through research. Classroom Action (CAR) with the title